Clinical predictors of left ventricular thrombus after myocardial infarction as detected by magnetic resonance imaging - Fardman, Alexander; Massalha, Eias; Natanzon, Sharon Shalom; Brodov, Yafim; Goitein, Orly; Chernomordik, Fernando; Herscovici, Romana; Grupper, Avishay; Kuperstein, Rafael; Mazin, Israel; Matetzky, Shlomi; Beigel, Roy (Frontiers in Cardiovascular Medicine, 2024)
Background The diagnosis of a left ventricular (LV) thrombus in patients with ST-segment elevation myocardial infarction (STEMI) remains challenging. The aim of the current study is to characterize clinical predictors for LV thrombus formation, as detected by cardiac magnetic resonance imaging (CMRI). Methods We retrospectively evaluated 337 consecutive STEMI patients. All patients underwent transthoracic echocardiography (TTE) and CMRI during their index hospitalization. We developed a novel risk stratification model (ThrombScore) to identify patients at risk of developing an LV thrombus. Results CMRI revealed the presence of LV thrombus in 34 patients (10%), of whom 33 (97%) had experienced an anterior wall myocardial infarction (MI), and the majority (77%) had at least mildly reduced left ventricular ejection fraction (LVEF < 45%). The sensitivity for thrombus formation of the first and second TTE was 5.9% and 59%, respectively. Multivariate logistic regression model revealed that elevated C-reactive protein levels, lack of ST-segment elevation (STe) resolution, elevated creatine phosphokinase levels, and STe in anterior ECG leads are robust independent predictors for developing an LV thrombus. These variables were incorporated to construct the ThrombScore: a simple six-point risk model. The odds ratio for developing thrombus per one-point increase in the score was 3.2 (95% CI 2.1–5.01; p < 0.001). The discrimination analysis of the model revealed a c-statistic of 0.86 for thrombus development. The model identified three distinct categories (I, II, and III) with corresponding thrombus incidences of 0%, 1.6%, and 27.6%, respectively. Conclusion ThrombScore is a simple and practical clinical model for risk stratification of thrombus formation in patients with STEMI.